2018
DOI: 10.1016/j.jchf.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Is Time of the Essence? The Impact of Time of Hospital Presentation in Acute Heart Failure

Abstract: In this AHF trial, patients admitted during off hours exhibited a distinct clinical profile, experienced greater dyspnea relief, and had lower post-discharge mortality than regular-hour patients. These findings have implications for future AHF trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…An analogous analysis of the ASCEND‐HF trial showed lower 180 day cardiovascular mortality among non‐working vs. working hour admission. Still, there were no differences when patients were divided in line with RELAX‐AHF nighttime vs. daytime admission criteria 7 . For the first time, the current analysis from REPORT‐HF showed higher mortality at 1 year follow‐up for patients presenting during non‐working vs. working hours.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…An analogous analysis of the ASCEND‐HF trial showed lower 180 day cardiovascular mortality among non‐working vs. working hour admission. Still, there were no differences when patients were divided in line with RELAX‐AHF nighttime vs. daytime admission criteria 7 . For the first time, the current analysis from REPORT‐HF showed higher mortality at 1 year follow‐up for patients presenting during non‐working vs. working hours.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, Western European patients were admitted more frequently during non‐working vs. working hours than Eastern European patients. This was also shown in the ASCEND‐HF but not RELAX‐AHF sub‐analysis 7,8 . Regional discrepancies with previous studies may be principally related to the variation of countries included in each region.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Most recently, a sub-analysis from ASCEND-AF showed that patients who presented during off hours profit more than do others from nesiritide. 17 In our study, we could show that NPs have a very strong prognostic impact, which is not only related to the diagnosis of AHF. Specifically, patients with ACS and COPD/pneumonia had the highest mortality when MR-proANP was >300 pmol/L.…”
Section: Figurementioning
confidence: 47%